NILAI-NILAI AJARAN ISLAM DAN ETIKA WIRAUSAHA DALAM PENDIDIKAN KEWIRSUSAHAAN - M Ilham Abdullah; Helmarini Helmarini (Jurnal Economic Edu, 2021)
Islamic values as universal truth of teachings and moral ethics are absolutely essential good deeds to be applied in daily life including in running an entrepreneurial business venture so that the multi-benefits of the success of business ventures and various positive impacts of business that benefit evenly for all parties can be achieved satisfactorily For ths reason enterpreunership education which contains islamic religion teaching and ethilues are considered very important and needs to be increased its quality so that the percentage of reliable entrepreneurs number in Indonesia who are still very few can be increased so that the prosperity of Indonesian people's lives can be realized evenly There are so lot of companies found that produce wares product or services both large and small are forced to close due to neglect ethical aspects in running their entrepreneurial business so that the number of workers who have to be laid off has made unemployment increasingly then number of criminal cases increases sharply as a result which could ultimately exacerbate the national security in our country Indonesia The purpose of writing this paper are to explain for answering the following questions 1) What is entrepreneurial ethics? 2) What are the principles of entrepreneurial ethics? 3) What are the factors that influence entrepreneurial ethics? 4) What are the goals and of applying Islamic religion teaching and ethics in entrepreneurship? 5) How do we implementate the entrepreneurial activities according to Islamic teachings? Keywords: Islamic Religion Teaching- Ethical values and Entrepreneurship Education